The Effect of Nasal Administration on the Management of Melasma -A Case Study: Life Science-Ayurveda - Kalyani, S.S.; R., Manu (International Journal of Life Science and Pharma Research, 2022)
Melasma is commonest among hyperpigmantation diseases which presents as irregularly shaped, but often distinctly defined as blotches of light to dark-brown pigmentation. It is a very common chronic disorder usually seen in women of childbearing age which is a frustrating condition to the women. There are 12.3% to 19.4% of world population suffering with this problem. Vyanga is one of the kshudra roga and is explained by Acharya Sushruta as painless thin brown patches over face. While considering the pathogenesis of vyanga, involvement of pitta is more and it is a rakta pradoshaja vyadhi. Depending on the pathogenesis and asrayaasrayi bhava of doshas involved, nasya(nasal route) is mainly indicated. By doing the nasya (nasal route) it it benefits in relieving the excess (pitta vriddi) pitta and also helps in varna prasadana(complexion). In this single case study, pratimarsha nasya was administered for 30 days continuously. The assessment criterias were noted before and after the treatment. Subjective parameters i.e Mukhamagatya mandalam (patches), Shyava varna(pigmentation), Kandu (itching), Parusha sparsha(dry skin) are the chief complaints of Vyanga and objective parameters such as MASI (Melasma area seviarity index). Assessments are done before and after the treatment. Symptoms of Melasma (Vyanga) decreased and it showed clinical progressiveness of the treatment given. In our study we found Color (pigmentation) of the leision had shown improvement .